anatomy of EXERCISE : - Manocchia, Pat (Firefly Books, 2008)
Anatomy of Exercise is revolutionary for its insights into how different muscles of the body actually work during exercise. The book is organized by body area and shows common sequences in the progression of a typical workout. Lifelike anatomical illustrations demonstrate each exercise and reveal in colorful detail exactly which muscles are engaged, which are being conditioned and how those muscles respond